The Effect of Self-Service Technology Service Quality on Customer Loyalty and Behavioral Intention - Radnan, Yokie; Christin, Velencia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
The purpose of this research is to know the effect of self-service technology service quality on customer loyalty, behavioral intention, and customer satisfaction, the effect of self-service technology service quality on customer loyalty and behavioral intention mediated by customer satisfaction, and the effect of self- service technology service quality on customer loyalty mediated by brand image. This study uses a quantitative approach using an online questionnaire data collection method (Google Form) and will be disseminated via social media (Line, WhatsApp, and Instagram). The sampling technique used in this study is non-probability sampling – purposive sampling with 218 respondents. The results of the research conducted prove that all hypotheses in the study are supported, including service quality self-service technology has a positive effect on customer loyalty, service quality self-service technology has a positive effect on behavioral intention, service quality self-service technology has a positive effect on customer satisfaction, customer satisfaction mediates the relationship between service quality self-service technology on customer loyalty positively, customer satisfaction mediates the relationship service quality self-service technology positively on behavioral intention, brand image mediates the relationship service quality self-service technology positively on customer loyalty.